Analisis Tingkat Pendapatan Usahatani Jambu Mete di Desa Lianosa Kecamatan Tongkuno Selatan Kabupaten Muna - Kaharuddin, Kaharuddin; Ola, Taane La; Yusria, Wa Ode (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The purpose of this study was to determine the income level of cashew farming in Lianosa Village, South Tongkuno District, Muna Regency. The population used in this study is all farmers who cultivate cashew plants. The number of farmers who cultivate cashew crops is 100 families. The sampling technique in this study was carried out by simple random sampling, which took 25% of the total number of farmers who cultivated cashew crops so that the number of respondents in this study was 25 families. The type of data used in this study is primary data, namely data obtained through direct interviews with respondent farmers. Secondary data are data obtained from local government institutions and related agencies and through library studies. The results of the study showed that the results of the analysis of income of cashew farming per harvest season in the study area for the 2018 harvest season were still low. The average total income obtained by farmers is Rp. 5,970,000. The average total cost of cashew farming is Rp.1,288,188, and the average total income earned by farmers is Rp. 4,681,812. This shows that the average total income obtained by farmers in the 2018 harvest season can cover all farming costs.